2005
DOI: 10.1080/13556210500123340
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of MDMA (Ecstasy) on the human central nervous system revealed by visual evoked potentials

Abstract: Several studies indicate long-term cognitive impairment of MDMA (ecstasy) users. In the present study we attempted to establish whether electrophysiological correlates of low-level cognitive processes present a long-term alteration, dependent on the level of use of ecstasy. We addressed this issue by investigating amplitude and latency of VEPs related to a very simple discrimination task involving sustained attention (arousal). Eight heavy-MDMA users, eight moderate-MDMA users and 18 drug-free control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Longer latencies and smaller amplitude of the P3 response are indicative of cognitive impairment. Diminished P3 potentials have been observed in heavy and moderate ecstasy user groups in simple discrimination tasks (Casco et al 2005) . Gamma et al (2005) report observable reductions in the P3 amplitudes of ecstasy users in a Go/No-go task compared to controls, though this could be a polydrug effect.…”
Section: Introductionmentioning
confidence: 99%
“…Longer latencies and smaller amplitude of the P3 response are indicative of cognitive impairment. Diminished P3 potentials have been observed in heavy and moderate ecstasy user groups in simple discrimination tasks (Casco et al 2005) . Gamma et al (2005) report observable reductions in the P3 amplitudes of ecstasy users in a Go/No-go task compared to controls, though this could be a polydrug effect.…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical and physiological abnormalities that have been reported in MDMA users include impulsivity (Morgan et al, 2006;Quednow et al, 2007), neuroendocrine dysfunction (Gerra et al, 1998(Gerra et al, , 2000(Gerra et al, , 2003McCann et al, 2000;Verkes et al, 2001), alterations in pain modulation (O'Regan and Clow, 2004), sleep architecture (Allen et al, 1993;Ricaurte and McCann, 2001), visual-evoked potentials (Casco et al, 2005), and event-related potentials (Mejias et al, 2005). Like cognitive function, all of these behavioral spheres are known to be influenced, in part, by brain 5-HT systems.…”
Section: Introductionmentioning
confidence: 99%
“…A diminished P3 potential is understood to reflect cognitive dysfunction. Casco et al (2005) observed a diminished P3 response in a simple discrimination task in moderate and heavy ecstasy users compared to controls in a visually evoked potential study. Furthermore Gamma et al (2005) report reductions in the P3 amplitudes of ecstasy users, compared to controls in an inhibitory control (Go-Nogo) task.…”
mentioning
confidence: 99%